On some normal forms in the fuzzy databases with linguistic data - Vinh, Lê Xuân; Thành, Trần Thiên; Việt, Lê Xuân (Journal of Computer Science and Cybernetics, 2013)
The viewpoint that each attribute domain of the fuzzy databases with linguistic data corresponds to an appropriate hegde algebras, the fuzzy functional dependencies and the fuzzy multivalued dependencies are studied. In this paper, we continue to study a number of fuzzy normal forms. Such concepts as k-keys, super k-keys and the normal forms F1NF, kF2NF, kF3NF, kFBCNF are defined in fuzzy databases with linguistic data. The paper focuses on researching the fuzzy dependency preserving decomposition into kF3NF and the lossless join decomposition into kFBCNF